2011
DOI: 10.1242/dev.069146
|View full text |Cite
|
Sign up to set email alerts
|

Complex interactions between cis-regulatory modules in native conformation are critical for Drosophila snail expression

Abstract: It has been shown in several organisms that multiple cis-regulatory modules (CRMs) of a gene locus can be active concurrently to support similar spatiotemporal expression. To understand the functional importance of such seemingly redundant CRMs, we examined two CRMs from the Drosophila snail gene locus, which are both active in the ventral region of pre-gastrulation embryos. By performing a deletion series in a ∼25 kb DNA rescue construct using BAC recombineering and site-directed transgenesis, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 43 publications
7
87
0
Order By: Relevance
“…To determine the feasibility of manipulating the timing of gene expression in the presumptive mesoderm, we placed the distal (shadow) snail enhancer ( snaE ) (Dunipace et al, 2011; Perry et al, 2010) upstream of the sna , sog , ths , and pnr promoters and yellow reporter gene (Figure 4A-C). We observed similar relative t50 values as those obtained with the pnr enhancer (Figure 3; Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the feasibility of manipulating the timing of gene expression in the presumptive mesoderm, we placed the distal (shadow) snail enhancer ( snaE ) (Dunipace et al, 2011; Perry et al, 2010) upstream of the sna , sog , ths , and pnr promoters and yellow reporter gene (Figure 4A-C). We observed similar relative t50 values as those obtained with the pnr enhancer (Figure 3; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A 25 kb snail BAC transgene encompassing the snail transcription unit, proximal enhancer, and neighboring Tim17B2 locus (which harbors the distal snail shadow enhancer) was shown to be sufficient to rescue the gastrulation defects of sna - / sna - mutant embryos (Dunipace et al, 2011; Perry et al, 2010). However, there is evidence that the proximal enhancer might attenuate snail expression by impeding access of the distal enhancer to the sna promoter (Dunipace et al, 2011) (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…However, in essence, these assays are reductionist, and test relatively short pieces of DNA sequences in isolation, which are usually randomly integrated into the genome, and therefore out of their natural genomic context. In several instances, enhancer elements at the endogenous locus do not recapitulate the activity that they showed when tested in enhancer assays [59][60][61]. The observed differences have been put down to non-additive activity of regulatory elements in their native region, or position effects owing to the genomic context where the element is inserted.…”
Section: Identifying Regulatory Elementsmentioning
confidence: 99%
“…These auxiliary enhancers are intrinsically capable of driving gene expression in a pattern similar to that of the primary enhancer. [10][11][12][13] Deletion of a shadow enhancer does not alter expression or fitness under optimal conditions, but compromises the ability of the system to buffer against noise. For example, a shadow enhancer identified downstream of the snail gene drives expression in a pattern broadly overlapping that of a previously characterized primary enhancer.…”
Section: Chromatin Occupancy Patterns Of the Ets Repressor Yanmentioning
confidence: 99%
“…Thus regulation through these two semi-redundant elements buffers snail expression against both environmental and genetic perturbation. Although our understanding of auxiliary enhancers is presently limited to these few examples, [10][11][12][13] their initial characterization underscores the importance of regulatory precision to developmental programs and suggests complex interactions between multiple cis-regulatory regions could provide diverse and widespread mechanisms for buffering gene expression. Here we present a speculative discussion of how regulation by the Drosophila ETS family transcriptional repressor Yan may confer robustness both at the level of individual gene expression and across developmental signaling networks.…”
Section: Chromatin Occupancy Patterns Of the Ets Repressor Yanmentioning
confidence: 99%